Improving the Students’ Reading Comprehension by Using Think Talk Write (TTW) - Yuliana Rosita; Karman Karman (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This research was designed to improve the students` reading comprehension through Think TalkWrite at the first-grade students of SMKN 1 Lasusua. The research problem was “The readingcomprehension of the first- grade students of SMKN 1 Lasusua is low”. The design of this researchwas collaborative Classroom Action Research (CAR).In this research, there were two cycles. Thefirst cycle was not success because the result of the students’ test did not fulfill the KKM, so therewas the next cycle. The second cycle was success because the result of the student test achieved the KKM mandatory by the school. In addition, this research must get score of 70 to fulfill theMinimum Mastery Criterion – Kriteria Ketuntasan Minimal (KKM). It could be seen in the averagescore, it was 68.6 in the first cycle, and there were only 17 students from 35 students got greater score than or equal 70. This score increased to be 74.77 in the second cycle, there were 26 from 35students got score greater than or equal 70. It means that this research was successful. Based onthe findings, the conclusion is Think Talk Write strategy could improve the students` comprehensionin reading at the first-grade students of SMKN 1 Lasusua